Exciton absorption spectrum of thin (KI)₁₋x(PbI₂)x films - Yunakova, O.N.; Miloslavskii, V.K.; Kovalenko, E.N. (Functional Materials, 2013)
The absorption spectra of thin films of (KI)₁₋x(PbI₂)x 0.1≤ x≤ 0.5 were investigated in the spectral interval 2–6 eV. The formation of two compounds KPbI₃ and K₄PbI₆ in system KI–PbI₂ was determined on the basis of the spectra analysis. It was shown, that exciton excitations in the investigated compounds are localized in sublattice containing lead ions and related to excitons of the intermediate bond.